2002
DOI: 10.1021/ed079p420
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Single Crystal X-Ray Diffraction in the Undergraduate Curriculum

Abstract: Florida Polytechnic University-a predominantly undergraduate institution and the newest member of the State University System of Florida-has recently entered into a strategic agreement with Rigaku Americas to develop an X-ray analytical capability that will enrich this new environment. A major component of this installation is the Rigaku SmartLab, a high-resolution state-of-the-art X-ray diffractometer that is capable of performing a wide variety of analytical functions. At Florida Poly, we have instituted a u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…proportionality constant: an overall scale factor, factors describing the diffractometer geometry in the so-called LP or Lorentz-polarization factor, and the reflection multiplicity m. m counts the number of symmetry equivalent reflections for each hkl. For example, in a tetragonal system, the (110) reflection has multiplicity 4 [(110), (-1-10), (-110), (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)]. All of these terms are described in full detail in most crystallography texts.…”
Section: Diffraction Fundamentalsmentioning
confidence: 99%
See 1 more Smart Citation
“…proportionality constant: an overall scale factor, factors describing the diffractometer geometry in the so-called LP or Lorentz-polarization factor, and the reflection multiplicity m. m counts the number of symmetry equivalent reflections for each hkl. For example, in a tetragonal system, the (110) reflection has multiplicity 4 [(110), (-1-10), (-110), (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)]. All of these terms are described in full detail in most crystallography texts.…”
Section: Diffraction Fundamentalsmentioning
confidence: 99%
“…It also leads to significant gaps developing between the theory students see in lectures and textbooks, and the way they experience crystallography in a practical setting. Several publications have previously raised the educational consequences, and there have been a number of earlier papers on how to build crystallographic education into school, undergraduate and postgraduate, curricula. Several previous publications have described ways in which powder diffraction experiments can be introduced into undergraduate practical classes to highlight the importance of the technique itself, , or its use as a characterization method as part of a wider laboratory practical. We are, however, unaware of other work that teaches structure analysis from powder diffraction data in the way described here.…”
Section: Introductionmentioning
confidence: 99%
“…In 1956, X-ray diffraction studies were first demonstrated as a valuable technique for characterizing essential oils and their derivatives . X-ray powder diffraction data on a variety of semicarbazone carbonyl type compounds including carvone were published by Meranger et al Recently, the incorporation of single-crystal X-ray diffraction into the undergraduate chemistry curriculum has since proven itself in terms of the pedagogical value and benefits to students. Despite the obvious benefits, the technique has not been adopted widely, primarily due to the expense of installing and maintaining the instrumentation needed. This experiment could become a virtual reality in the absence of equipment (see instructor Supporting Information).…”
Section: Introductionmentioning
confidence: 99%
“…The established model for practical training at the University of Southampton places first and second year undergraduates into teaching laboratories, following prescribed methods in large group sizes and gaining foundational experience in common analytical techniques, e.g., infrared (IR) and precollected nuclear magnetic resonance (NMR) spectra. However, access to advanced characterization techniques, specifically hands-on X-ray crystallography, at the undergraduate level is restricted, mainly due large to group sizes and scarce resources. These techniques would only be (partly) experienced in the latter stages of a degree if an embedded research project were undertaken.…”
Section: Introductionmentioning
confidence: 99%